Charles de Gaulle's Paradox - M. D. Romanova (Vestnik MGIMO-Universiteta)
In article events of student's mutiny of 1968 which happened in France in the period of Charles de Gaulle's board from the axiological point of view are considered. The main reasons for excitements, change of cultural values of society after war are analysed. As a result of the theoretical analysis the conclusion is drawn that crisis of domestic policy of Charles de Gaulle was in many respects caused by change of cultural installations of new generation.